2019
DOI: 10.1016/j.clnu.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetarian diets on the presentation of metabolic syndrome or its components: A systematic review and meta-analysis

Abstract: VD in comparison with omnivorous diet is not associated with a lower risk of MetS based on results of meta-analysis of cross-sectional studies. The association between VD and lower levels of SBP, DBP, HDL-C, and fasting glucose is uncertain due to high heterogeneity across the cross-sectional studies. Larger and controlled studies are needed to evaluate the association between VD and MetS and its components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 73 publications
4
23
0
Order By: Relevance
“…However, as expected, several of the observed associations between diet and cardiovascular risk factors other than BMI seemed to be mediated by BMI, supporting the hypothesis that vegetarian diets may lead to a lower BMI, which could then result in a decrease in cardiovascular risk factors. Overall, our findings confirm the previous results from cross-sectional studies and prospective cohorts (43)(44)(45) on the positive link between different vegetarian diets and a positive cardiometabolic profile (17,20,(46)(47)(48)(49)(50) .…”
Section: Vegetarian Diets In a Swiss Urban Populationsupporting
confidence: 91%
“…However, as expected, several of the observed associations between diet and cardiovascular risk factors other than BMI seemed to be mediated by BMI, supporting the hypothesis that vegetarian diets may lead to a lower BMI, which could then result in a decrease in cardiovascular risk factors. Overall, our findings confirm the previous results from cross-sectional studies and prospective cohorts (43)(44)(45) on the positive link between different vegetarian diets and a positive cardiometabolic profile (17,20,(46)(47)(48)(49)(50) .…”
Section: Vegetarian Diets In a Swiss Urban Populationsupporting
confidence: 91%
“…In other large population surveys, risks for cardiovascular disease, type 2 diabetes, and all-cause mortality were reduced for the ‘healthy’ plant-based diet group compared to the ‘unhealthy’ plant-based diet group, which supports the contention that not all plant-based diets are equal [10,11,29]. Considering these findings, and that much of the published research on plant-based or vegetarian diets and health outcomes did not account for diet quality [30,31], it is possible that the purported benefits of ‘healthful’ plant-based diets may be moderated and underreported.…”
Section: Discussionsupporting
confidence: 54%
“…Some studies found that individuals who restrict the intake of animal-based foods (meat, poultry, fish) have favorable metabolic profiles (lower body mass index [BMI], lower blood pressure, lower fasting glucose) [5,6], but others reported no association [7,8] or adverse associations [9][10][11]. However, many of these studies primarily used a cross-sectional study design and limited assessment of dietary intake to only animal foods [5,6]. Intake of plant foods, particularly less-healthy plant foods, such as refined carbohydrates or plant foods high in sugar (e.g., sugar-sweetened beverages) and salt have not been taken into account in these prior studies.…”
Section: Introductionmentioning
confidence: 99%